'Anne goes rogue for abortion rights!': Hashtag feminism and the polyphonic nature of activist discourse. (February 2019) - Myles, David
In the emerging context of hashtag feminism, this article explores the #SupportIslandWomen pro-choice initiative in Prince Edward Island (PEI), Canada. The movement gained visibility by using the altered image of Anne of Green Gables (rogue Anne) on posters and graffiti throughout PEI and on social media. Drawing from organizational discourse theory, we analyse how rogue Anne was invoked by activists who spoke in her name, thus enacting the polyphonic nature of discourse. Our case study was built by performing non-participant observation online and by conducting a search in Canadian blogs and newspapers. First, we detail the discursive practices developed within the #SupportIslandWomen movement and underline their constitutive effects, namely, by focusing on the organizing properties of the hashtag feature. Then, we investigate the benefits and limitations of using rogue Anne as a unifying symbol and reflect on the discursive struggles that led to and were generated by her usurpation.